Case report: A case of effective treatment of primary myelofibrosis with nodular panniculitis using ruxolitinib combined with corticosteroids - Wufuer, Guzailinuer; Zhao, Jia-Lin; Huang, Qin; Babayi, Ainiwaer; Abudureyimu, Dilinuer; Mao, Min; Duan, Ming-hui (Frontiers in Oncology, 2024)
We report the case of a 54-year-old healthy Han Chinese male presenting with fever, pallor, erythematous subcutaneous nodules on the limbs, and significant anemia as indicated by routine blood tests, with no response to antimicrobial therapy. Initial skin biopsy was inconclusive. The erythematous subcutaneous nodules on the limbs rapidly progressed to widespread subcutaneous nodules across the body, with worsening anemia. Bone marrow biopsy revealed multifocal fibroblastic proliferation with focal fibrosis, classified as MF-2, and positive for the JAK2V617F mutation alongside SRSF2 positivity. Whole-body PET-CT scans did not reveal any lymph nodes or suspect lesions with high SUV uptake. A subsequent skin biopsy identified the condition as nodular panniculitis (NP), leading to a final diagnosis of primary myelofibrosis(PMF)with NP. The patient initially received treatment with oral ruxolitinib and prednisone acetate, resulting in normalization of body temperature, resolution of erythematous nodules, and normalization of blood parameters.